2020
DOI: 10.4269/ajtmh.19-0779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual and Combined Water, Sanitation, Handwashing, and Nutritional Interventions on Child Respiratory Infections in Rural Kenya: A Cluster-Randomized Controlled Trial

Abstract: Poor nutrition and hand hygiene are risk factors for acute respiratory infections (ARIs). Safe drinking water and sanitation can reduce exposure to pathogens and encourage healthy immune responses, reducing the risk of ARIs. Within a trial assessing impacts of water, sanitation, and handwashing (WASH), and nutritional interventions, we evaluated effects on ARIs. The WASH Benefits cluster-randomized trial enrolled pregnant women from Kenyan villages and evaluated health outcomes in children born to enrolled mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The WASH Benefits Kenya and Bangladesh trials provided latrine upgrades, child feces management tools, and behavioral promotion in rural Kenya and Bangladesh. The Kenya trial found no effect on diarrheal disease [17], soil-transmitted helminth infections [19], and ARI [20] from the sanitation intervention. In Bangladesh, the sanitation intervention led to prevalence reductions of 39% for diarrheal disease, 25% for Giardia infections, 29% for Trichuris trichiura infections, and 25% for ARI [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The WASH Benefits Kenya and Bangladesh trials provided latrine upgrades, child feces management tools, and behavioral promotion in rural Kenya and Bangladesh. The Kenya trial found no effect on diarrheal disease [17], soil-transmitted helminth infections [19], and ARI [20] from the sanitation intervention. In Bangladesh, the sanitation intervention led to prevalence reductions of 39% for diarrheal disease, 25% for Giardia infections, 29% for Trichuris trichiura infections, and 25% for ARI [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, children receiving WSH and nutrition interventions had reduced prevalence of diarrhea 20 and respiratory infections 21 compared to controls. In Kenya, children receiving the nutrition intervention had marginally lower prevalence of respiratory infections than controls; there were no other intervention effects 22,23 . In both countries, the nutrition intervention improved child linear growth 20,22 .…”
Section: Introductionmentioning
confidence: 92%
“…Untuk mengatasi tantangan yang ditimbulkan oleh faktor lingkungan pada penyakit menular, sangat penting untuk menerapkan intervensi yang meningkatkan praktik air, sanitasi, dan kebersihan (WASH), serta intervensi gizi. Sebagai contoh, uji coba acak klaster WASH Benefits di Kenya mengevaluasi dampak intervensi air, sanitasi, cuci tangan, dan gizi secara individu dan gabungan terhadap infeksi saluran pernapasan anak (Swarthout et al, 2020). Intervensi semacam itu dapat membantu mengurangi paparan terhadap patogen dan mendorong respons kekebalan tubuh yang sehat, yang pada akhirnya mengurangi risiko penyakit menular.…”
Section: Literature Review a Kesehatan Lingkungan Dan Penyakit Menularunclassified